High prevalence of virological failure and HIV drug mutations in a first-line cohort of Malawian children. (29th August 2018) - Huibers, M H W; Moons, P; Cornelissen, M; Zorgdrager, F; Maseko, N; Gushu, M B; Iwajomo, O H; Boele van Hensbroek, M; Calis, J C J
Abstract: Background: Drug resistance mutations (DRMs) increasingly jeopardize paediatric HIV programmes in sub-Saharan Africa. As individual monitoring of DRMs and viral loads has limited availability, population data on DRMs are essential to determine first-line susceptibility. Paediatric data from sub-Saharan Africa are scarce and unavailable for Malawi. Objectives: To determine the prevalence of virological failure (VF) and DRMs among ART-naive HIV-infected Malawian children during the first year of first-line ART. Methods: In a prospective cohort of HIV-infected Malawian children, on first-line treatment, children were followed monthly; blood was collected for viral load testing (6 and 12 months) and genotypic resistance testing (12 months). VF was defined as at least one viral load >1000 copies/mL or death after 6 months of ART. DRMs were identified and susceptibility to NRTIs and NNRTIs was scored using the Stanford algorithm and by calculating genotypic susceptibility scores (GSSs). Results: VF occurred in 66% (23/35) of the children during 12 months of follow-up. DRMs were detected in 44% (15/34); all had NNRTI resistance and 12% (4/34) had dual-class NNRTI/NRTI resistance. Reduced susceptibility (DRMs and GSS <3) was seen in 41% (14/34) to their current first-line regimen. High-level resistance was most common for nevirapine [26% (9/34)]. Conclusions: In this first report on VF and DRMs in children on first-line ART in Malawi, the rates of VF and DRMs were alarmingly high. Paediatric HIV programmes in sub-Saharan Africa should emphasize programmatic evaluation of VF and include detection of DRMs to adjust and design adequate first- and second-line regimens and prevent widespread resistance in children.